Islamic Education Policy in Dealing with Social Change - Muhammad Faiq Haqqoni; Ahmad Subagyo; Muhammad Sofian Hadi (Journal of Educational Management Research, 2025)
In the face of increasingly complex social changes, Islamic educational institutions are required to have policies that are adaptive and relevant to the evolving dynamics of society. Pesantren, as a traditional institution, faces a significant challenge in upholding Islamic values while addressing contemporary issues such as moral crises, digital disruptions, and cultural diversity. This study aims to examine Islamic education policies in response to social change in schools, with an emphasis on the policy of forming socio-spiritual character and value integration strategies in the curriculum, as well as the institutional challenges faced. This study employs a descriptive qualitative approach, utilizing data collection techniques that include observation, documentation, and interviews. The results of the study show that this school implements progressive and responsive education policies by integrating Islamic values into contextual programs. However, cultural resistance and institutional limitations are still obstacles to optimizing policies. This study contributes to the development of a contextual and transformational model for Islamic education policy.